Driver mutations in TP53 are ubiquitous in high grade serous carcinoma of the ovary. - Ahmed, A; Etemadmoghadam, D; Temple, J; Lynch, A; Riad, M; Sharma, R; Stewart, C; Fereday, S; Caldas, C; Defazio, A; Bowtell, D; Brenton, J (2010)
Numerous studies have tested the association between TP53 mutations in ovarian cancer and prognosis but these have been consistently confounded by limitations in study design, methodology, and/or heterogeneity in the sample cohort. High-grade serous (HGS) carcinoma is the most clinically important histological subtype of ovarian cancer. As these tumours may arise from the ovary, Fallopian tube or peritoneum, they are collectively referred to as high-grade pelvic serous carcinoma (HGPSC). To identify the true prevalence of TP53 mutations in HGPSC, we sequenced exons 2-11 and intron-exon boundaries in tumour DNA from 145 patients. HGPSC cases were defined as having histological grade 2 or 3 and FIGO stage III or IV. Surprisingly, pathogenic TP53 mutations were identified in 96.7% (n = 119/123) of HGPSC cases. Molecular and pathological review of mutation-negative cases showed evidence of p53 dysfunction associated with copy number gain of MDM2 or MDM4, or indicated the exclusion of samples as being low-grade serous tumours or carcinoma of uncertain primary site. Overall, p53 dysfunction rate approached 100% of confirmed HGPSCs. No association between TP53 mutation and progression-free or overall survival was found. From this first comprehensive mapping of TP53 mutation rate in a homogeneous group of HGPSC patients, we conclude that mutant TP53 is a driver mutation in the pathogenesis of HGPSC cancers. Because TP53 mutation is almost invariably present in HGPSC, it is not of substantial prognostic or predictive significance.